(untitled) (Perner’s Contacts, 2016)
The paper follows on previous author’s paper about effects of ETCS on braking curves. In this paper are compared two Baselines (2 and 3) from the angle of set-up of OBU. There are some parameters which are different and they have influence of the braking curve. The simulation of those parameters has been done and results are presented in this paper.